Bangladesh : Report on Observance of Standards and Codes-Fiscal Transparency. (IMF Staff Country Reports; Country Report ;, 2003)
This report assesses the Observance of Standards and Codes on Fiscal Transparency for Bangladesh. Bangladesh has made significant progress in recent years toward addressing longstanding problems of fiscal reporting and meeting basic requirements of fiscal transparency. Measures are in hand to present audited accounts from 2002/3 onward within 12 months of year-end, and monthly reports are being produced about 5-8 weeks after month-end. Much remains to be done to improve data reliability, particularly with respect to reporting of foreign-financed projects, but processes are in place to establish sustainable improvements in accounts reconciliation.